Business Development Strategy of Sweet Milo's Current Business to Increase the Entrepreneurship Spirit in Students Using Technology 4.0 - Gita, Indah; Rejabbilaisyah, Rejabbilaisyah; Ardiansyah, Septo (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
The beverage business is one of the most promising businesses in the modern era. Many people are hunting for drinks that are attractive and look delicious. In the current era, digital media in the form of social media continues to grow and can be used to sell the beverage business. Apart from being liked by the public, this beverage business is also very popular with new business entrepreneurs, this is because the capital used is small but it can benefit culinary entrepreneurs. Currently, various brands and types of contemporary drinks continue to emerge in Indonesian society. One type of contemporary drink is the Millo drink which is combined with boba or jelly. This drink has become a popular drink and is loved by teenagers and young adults. Strategic planning for business development needs to be made so that industrial operations can run effectively and efficiently. This study uses descriptive qualitative research methods with the help of SWOT analysis. This method is able to analyze strengths, weaknesses, opportunities and threats. The data collection technique used in this study was using a needs questionnaire which was distributed directly to PGPAUD students. This research was conducted in the city of Bengkulu in March. In this study using direct observation techniques and distributing questionnaires filled out by students to find out the taste and quality of sweet milo drinks.